ANALISIS KESULITAN BELAJAR FISIKA PADA MATA KULIAH IPA TERPADU MAHASISWA JURUSAN PENDIDIKAN BIOLOGI - Hasbiyati, Haning (Pendidikan Biologi,Universitas Islam Jember, 2014)
Has conducted research aimed to analyze the factors that cause learning difficulties in physics in integrated science subjects Biology Education majors, especially students of 6th semester of 2013/2014. The instrument in this study is a questionnaire Physics student learning difficulties. Based on the data and the results of the data analysis that the factors that cause learning difficulties Biological physics student education is a very influential factor on the internal aspects of interest precisely with the percentage of 81.5% and the effect of influential factors with the largest percentage of the motivational aspects of 78.6%. External factors that affect the largest percentage of the aspects of learning methods varied by 79% and fascinating aspects of the media on the indicator with a percentage of 80%.